The relationship between fear of movement, pain and fatigue severity, dyspnea level and comorbidities in patients with chronic obstructive pulmonary disease. Issue 18 (28th August 2019) - Vardar-Yagli, Naciye; Calik-Kutukcu, Ebru; Saglam, Melda; Inal-Ince, Deniz; Arikan, Hulya; Coplu, Lutfi
Abstract: Purpose: Dyspnea, sedentary lifestyle, and comorbid diseases may reduce the desire to engage in physical movement in chronic obstructive pulmonary disease (COPD). The aims of this study were to assess levels of kinesiophobia among stable COPD patients and evaluate the relationship between kinesiophobia and pain and fatigue severity, dyspnea level, and comorbidities in this patient group. Material and Methods: Thirty-one patients with moderate/severe COPD and thirty-one age- and sex-matched healthy controls participated in the study. All participants were assessed using Visual Analog Scale for pain severity, Fatigue Severity Scale, modified Medical Research Council Dyspnea Scale, Charlson Comorbidity Index, and Tampa Scale of Kinesiophobia. Results: Ninety-three percent of the patients with COPD had a high degree of kinesiophobia (Tampa Scale of Kinesiophobia score >37). The modified Medical Research Council Dyspnea Scale, Charlson Comorbidity Index, and Tampa Scale of Kinesiophobia scores of patients with COPD was significantly higher than those of healthy subjects ( p  < 0.001). Tampa Scale of Kinesiophobia score was significantly associated with modified Medical Research Council Dyspnea Scale score ( r  = 0.676, p  < 0.001), Charlson Comorbidity Index score ( r  = 0.746, p  < 0.001) and fatigue severity level ( r  = 0.524, p  = 0.005). Conclusion: Most moderate/severe COPD patients express fear of movement. Kinesiophobia is strongly associated with dyspnea perception, fatigue severity, multisystemic comorbidities in COPD. Further studies are needed to determine the effects of kinesiophobia on the success of pulmonary rehabilitation. Implications for rehabilitation: Most of moderate-to-severe chronic obstructive pulmonary disease patients have fear of movement. Increase fear of movement in moderate–severe chronic obstructive pulmonary disease is associated with increased dyspnea perception and fatigue severity and multisystemic comorbidities.